PELANGGARAN PRINSIP KERJA SAMA DALAM NOVEL TERJEMAHAN “ANIMAL FARM” KARYA GEORGE ORWELL - Bintang, Adinda; Baroroh, Hilma Erfiani (Bahtera Indonesia, 2026)
This research aims to describe the violations of the cooperative principle in George Orwell's novel titled Animal Farm (translation: Republik Hewan). The method used in this study is a qualitative descriptive approach. The data collection technique employed in this research is document analysis (documentation), which involves repeated readings and then transcribing dialogues. The data analysis technique for this study uses content analysis by identifying dialogues and character utterances that violate the cooperative principle, followed by interpreting the findings based on Grice's theory of cooperative principles. The results show that violations of the maxim of quality dominate, with a percentage of 40%, followed by violations of the maxim of quantity and maxim of relevance, each at 20%, and dual violations involving the maxims of quality and quantity also at 20%. Based on the research findings, the character Squealer dominates the violations of the cooperative principle in the novel because Squealer is a spokesperson and disseminator of propaganda, resulting in utterances that are excessive, irrelevant, and based on unsubstantiated information.